2005
DOI: 10.1111/j.1445-2197.2005.03552.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, morbidity and functional outcome after total or subtotal abdominal colectomy in the asian population

Abstract: Subtotal or total colectomy is associated with a good functional outcome and most patients were satisfied with their bowel function on follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…However, the presence of associated comorbidities has also being shown to be an important risk factor for death (21), which was present in over 60% of our patients. The mean length of stay is similar to other series of comparable patients (22) and functional outcome although not formally accessed with quality of life scores was good and in keeping with the published literature (22,23).…”
Section: Discussionsupporting
confidence: 86%
“…However, the presence of associated comorbidities has also being shown to be an important risk factor for death (21), which was present in over 60% of our patients. The mean length of stay is similar to other series of comparable patients (22) and functional outcome although not formally accessed with quality of life scores was good and in keeping with the published literature (22,23).…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the previously reported finding of three to four stools daily after TC-IRA; 25 percent of patients had more than five stools daily. 26 Concurrent analyses indicated restrictions on preoperative social activity, housework, recreation, and travel after TC-IRA. These were observed despite significant behavioral adaptation (e.g., dietary modification and use of antidiarrhea medications) as well as physiologic adaptation (e.g., ileum increasing its absorptive and receptive capacity) after STC-ISA and TC-IRA.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates of 11% to 32% had been reported from individual institutions. A closer figure to compare would be a study in Singapore that reported morbidity rate of 42% and 30‐day mortality rate of 10% [14]. However, the study included only total or subtotal colectomy and only 74% of all cases were performed in emergency setting.…”
Section: Discussionmentioning
confidence: 99%